Analisis Usaha Jasa Seventeen Voucher Sebelum dan Setelah Dilakukannya Penerapan Business Model Canvas : Erianti Enji, Sabinus Beni - Erianti Enji; Sabinus Beni (Universitas Indo Global Mandiri, 2023)
This research discusses the application of Business Model Canvas (BMC) on Seventeen Voucher service business before and after implementation, using SWOT analysis to identify strengths and weaknesses. The study aims to provide insights for business owners in developing effective business strategies and improving customer satisfaction. The data was collected through observation, in-depth interviews, and documentation, and analyzed using qualitative and SWOT analysis methods.The results show that the target customer segment is students in and around the campus, the value proposition is providing convenient services for internet-related needs, and the channels used are WhatsApp Business andFacebook. The study also identifies areas for improvement in customer relationship management and cost structure.The research discusses the evaluation of the Business Model Canvas (BMC) implementation in Seventeen Voucher service business and its analysis using SWOT analysis. The study found that affordable prices, promotions, and social media usage for promotion are factors that attract customers. Quality of service, reliability, responsiveness, and assurance are also important factors in customer satisfaction. Pricing is determined by observing the market and adjusting to customerdemand. The BMC helps simplify and communicate business strategies effectively. Overall, the study provides valuable insights for business owners in developing effective business strategies and improving customer satisfaction. The use of the BMC and SWOT analysis methods can help businesses identify their strengths and weaknesses, and develop strategies to improve their performance. The findings of this study can be useful for businesses in various industries, especially those targeting student customers and in the business progress.Keywords: Analysis, SWOT and Business Model Canvas